Microvascular hand surgery for digital ischemia in scleroderma. Issue 2 (June 2020) - Satteson, Ellen S; Chung, Melody P; Chung, Lorinda S; Chang, James
Periarterial sympathectomy and arterial bypass are microsurgical techniques which the literature suggests can provide improvement in digital pain and ulceration in patients with systemic sclerosis who have persistent symptoms despite medication management. This review summarizes the relevant anatomy, medical therapies, operative techniques, and surgical outcomes and complications associated with the management of the vascular manifestations of systemic sclerosis in the hand. Multidisciplinary collaboration between dermatology, rheumatology, and hand surgery can facilitate optimal medical and surgical management for systemic sclerosis patients.